Pengaruh Pengendalian Intern Kredit, Likuiditas, dan Ukuran Perusahaan pada Kemampulabaan LPD di Kota Denpasar - Janawati, Ni Wayan Jessy; Badera, I Dewa Nyoman (E-Jurnal Akuntansi, 2018)
The development of LPD in Denpasar the last ten years has shown positive trends in terms of assets, credit disbursed, and profit earned. This study aims to determine the effect of internal control of credit, liquidity, and company size on the LPD’s profitability in Denpasar City. The research was conducted all LPD in Denpasar City. The samples were obtained by 35 with saturated sampling technique. Data were analyzed using multiple linear regression. The level of internal credit control is measured by distributing questionnaires to each LPD in Denpasar City, liquidity is measured using Loan to Deposit Ratio (LDR), firm size with Ln total assets, and profitability measured by Return on Asset (ROA) ratio. F-test results show that independent variables simultaneously affect the LPD’s profitability in the city of Denpasar. The result of statistical t-test shows that internal control of credit and liquidity have positive effect on profitability, but firm size variable has no effect on profitability.  Keywords : LPD, profitability, internal credit control, liquidity, company size